Report by Professor D'Arcy Thompson on his mission to the Behring Sea in 1896, dated March 4, 1897. - Thompson, D'Arcy Wentworth, 1860-1948. (London : Printed for H.M.S.O. by Harrison & Sons, 1897)
Mode of access: Internet.